2015
DOI: 10.1007/s00520-015-3064-3
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to detect an improvement in cancer pain management? A comparison of two Norwegian cross-sectional studies conducted 5 years apart

Abstract: Is it possible to detect an improvement in cancer pain management? A comparison of two Norwegian cross-sectional studies conducted five years apart.Purpose: Cancer pain (CP) management is challenging. In recent years, efforts were undertaken to achieve better CP management, e.g. clinical research, new treatment modalities, development of guidelines, education, and focus on implementation. The aim of the present study was to compare the prevalence and characteristics of pain and breakthrough pain (BTP) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
8
2
1
Order By: Relevance
“…In our study, 56% of the patients reported pain (47% with local and 65% with advanced disease) compared to a Norwegian study, where the prevalence of pain among inpatients with either local or advanced cancer varied between 53% and 55% and among outpatients between 35% and 39% (26). In the present study, moderate or severe pain was reported by 5% of patients with local disease and 16% of patients with advanced disease.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In our study, 56% of the patients reported pain (47% with local and 65% with advanced disease) compared to a Norwegian study, where the prevalence of pain among inpatients with either local or advanced cancer varied between 53% and 55% and among outpatients between 35% and 39% (26). In the present study, moderate or severe pain was reported by 5% of patients with local disease and 16% of patients with advanced disease.…”
Section: Discussioncontrasting
confidence: 60%
“…Our findings are partly in line with a Norwegian study describing pain intensity in cancer patients treated at a tertiary cancer unit. The authors had concluded that no significant change occurred in experienced pain from 2008 to 2014 (26). There are several possible explanations for the lack of improvement in HRQoL and symptom control in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite huge resources allocated for research, teaching, and treatment, pain is still prevalent among patients with cancer (1)(2)(3). Barriers to improved cancer pain management are identified (4,5), strategies to overcome the barriers are demonstrated (6,7), and guidelines for treatment of cancer pain are published (8).…”
Section: Introductionmentioning
confidence: 99%
“…Pain prevalence and pain control may have changed during the following years [ 36 ]. However, a recent study found no improvement in cancer pain management in a 5-year perspective from 2008 [ 37 ]. Furthermore, the study population is patients with advanced cancer, limiting the generalizability of the conclusions.…”
Section: Discussionmentioning
confidence: 99%